Social costs of desertification in Africa: the case of migration - (:unkn) unknown (My University, 2006)
The paper discusses the links between migration and desertification in Africa. As this issue is not the subject of any specific recorded study, it is based on available localized work on migration, as well as reports on the rural exodus. “Migrations and development” is a theme that questions the use of the transfer of migrants to combat desertification. It proposes a qualitative inventory of the costs of migration and demonstrates how it reflects the absence of locally adapted agricultural policies and the development of internal markets, as well as the global treatment of inequalities between industrialized and developing countries.
Keywords: African Research